From Southeast Asia to Indo-Pacific: How Far Indonesian Geostrategic Doctrine Shapes Its Position - Jacob Junian Endiartia (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
Geographically, Indonesia is one of country that has so many potentials. With its location between two continents and oceans, Indonesia could make strategic role in region and the world. Geostrategy of one country play an important role to its foreign policy and diplomacy. Indonesia has ‘national resilience’ as the national geostrategic doctrine. It will be interesting to study how far that geostrategic doctrine influences international relations of Indonesia. This study will discuss in several parts, from the role of Indonesia as a part of middle-power countries in different government administration to the position of Indonesia in the region because of its geostrategic doctrine.